Retrospective determination of whether famine existed in Niger, 2005: two stage cluster survey. (2nd October 2008) - Reza, Avid; Tomczyk, Basia; Aguayo, Victor M; Zagré, Noel M; Goumbi, Kadadé; Blanton, Curtis; Talley, Leisel
Abstract : Objective To apply the famine scale by Howe and Devereux to the situation in Niger, west Africa, in 2005 to retrospectively determine whether famine existed. Design Two stage cluster survey. Setting Survey of households in each of Niger's eight regions. Participants 4003 households. Main outcome measures Crude mortality, mortality in children under 5, and the proportion of caregivers both nationally and regionally adopting coping strategies to deal with insufficient food needs. Results The estimated national crude mortality rate was 0.4 (0.4 to 0.5) deaths per 10 000 per day and under 5 mortality rate was 1.7 (1.4 to 1.9) deaths per 10 000 per day. Nationally, 22.3% (95% confidence interval 19.9% to 24.8%) of caregivers of under 5s did not resort to any coping strategies to deal with insufficient food needs. Reversible coping strategies were, however, used by 5.8% (4.7% to 7.0%) of caregivers, whereas 49.4% (46.9% to 51.8%) relied on irreversible coping strategies and 22.6% (20.0% to 25.4%) on survival strategies. Conclusion On the basis of the famine scale proposed by Howe and Devereux, most regions in Niger experienced food crisis conditions and some areas approached famine proportions.